Vaping topography and reasons of use among adults in Klang Valley, Malaysia - Zainol Abidin, Najihah; Zainal Abidin, Emilia; Zulkifli, Aziemah; Syed Ismail, Sharifah Norkhadijah; Karuppiah, Karmegam; Amer Nordin, Amer Siddiq; Musbah, Zuraidah; Zulkipli, Nur Fadhilah; Praveena, Sarva Mangala; Rasdi, Irniza; Abd Rahman, Anita (Asian Pacific Organization for Cancer Prevention, 2018)
Background: Consistency and accuracy of results in assessing health risks due to vaping or e-cigarette use are difficult to achieve without established consumption data. The present report covers baseline data on vaping topography and reasons for use among local users in Klang Valley, Malaysia. Methods: An 80-item survey regarding socio-demographic characteristics, smoking topography and reasons for e-cigarette use was employed to assess e-cigarette users recruited from several public universities and private organisations. The survey questionnaire was self-administered. Data were analysed using statistical software. Results: Eighty-six current e-cigarette users participated with more than half (51.2%) of them aged ≥ 25 years old. Significant proportions of the sample were single (51.2%), had a tertiary education level (63.5%) and a household income of less than USD1000 per month (65.2%). Median duration of e-cigarette use was less than a year; users drew approximately 50 puffs per day and refilled twice a day. The majority (74%) used e-liquids containing nicotine with a concentration of 6 μg/mL. Daily users spent USD18-23 per month. Reasons for using the e-cigarette included enjoyment of the products (85.9%), perception of lower toxicity than tobacco (87%), and the fact that it was a cheaper smoking alternative (61%). Conclusion: The data on e-cigarette smoking topography obtained in this study are novel. The reasons of usage were mainly users’ enjoyment of e-cigarettes, preparation for quitting smoking, perception of low toxicity and a healthier smoking substitute and cheapness in the long run. The results establish basic knowledge for the local vaping topography and reference material for future e-cigarette-related research.